1993
DOI: 10.1038/jcbfm.1993.20
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vulnerability of White Matter during Spinal Cord Ischemia

Abstract: The long-term effects of spinal cord ischemia were studied in 21 rats by lesion scores (LS, n = 21), somatosensory evoked potentials (SEP, n = 16), electromyographic measurements (EMG, n = 12) and histology of the spinal cord (n = 21) 48.5 +/- 57.2 days after 10- to 12-min occlusion of the thoracic aorta and subclavian arteries. All the animals were initially paraplegic with a spastic presentation but seven recovered within 2 days (group A), demonstrating low LS (3.4 +/- 1.05) normal EMGs (n = 3) and unremarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 13 publications
1
29
0
1
Order By: Relevance
“…Although studies have demonstrated that white matter is susceptible to ischemic injury, the mechanisms of white matter injury are not well characterized. 7,14 In contrast to gray matter ischemia, in vitro studies suggest that activation of glutamate receptors may not be a key event in the mediation of ischemic cerebral white matter injury. Recent studies suggested some possible explanations for ischemic white matter injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated that white matter is susceptible to ischemic injury, the mechanisms of white matter injury are not well characterized. 7,14 In contrast to gray matter ischemia, in vitro studies suggest that activation of glutamate receptors may not be a key event in the mediation of ischemic cerebral white matter injury. Recent studies suggested some possible explanations for ischemic white matter injury.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of morphological changes in the white matter of the rat spinal cord 1 to 2 months after transient ischemia have been previously reported. 8,24 In one of these studies, degenerating axons containing aggregates of microtubules and dense bodies, disintegrating myelin sheaths, and scavenger cells were seen in the corticospinal tract of the lumbar cord 32 days after injury. 23 The postischemic loss of axons in the white mater of the 4th lumbar spinal cord segment may have resulted from local axonal injury or from a lesion in the more proximal axonal segments up to their cell bodies.…”
Section: White Matter Damage After Spinal Cord Ischemiamentioning
confidence: 99%
“…The conventional view that the white matter is less vulnerable to ischemic injury as compared with the gray matter is now being questioned. Increasing in vivo evidence indicates that ischemia may primarily damage white matter in the spinal cord 8 and the brain. 9,10 Whereas excitotoxins play a major role in the pathogenesis of ischemic gray matter injury, 4 the role of glutamate receptor action in ischemic white matter lesion is less clear.…”
Section: See Editorial Comment Page 1952mentioning
confidence: 99%
“…After 9 minutes of occlusion, motor dysfunction was severe, but it was reversible at 2 days. Pathology was limited to intermediate gray and dorsal horns predominantly, [17][18][19][20][21] with preservation of anterior horns. After occlusion for 11 minutes, neurological deficits were severe, with persistent paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Animal models of spinal cord ischemia have been described in the literature with variable reproducibility. [11][12][13][14][15][16][17][18][19][20][21] Zivin et al 15,16 developed a highly reproducible model in the rabbit that has become the standard for the study of experimental spinal cord ischemia. In the rabbit, transient occlusion of the infrarenal segment of aorta causes…”
mentioning
confidence: 99%